1979
DOI: 10.1002/cjce.5450570613
|View full text |Cite
|
Sign up to set email alerts
|

A novel magnetoelectrolytic reactor

Abstract: The characteristics of mass transport and cathode deposit in a pilot‐plant size magnetoelectrolytic reactor employing an anisotropic inhomogencous magnetic field are analyzed. It is shown that the behaviour of the reactor, especially the deposition pattern, is strongly linked to the distribution of the magnetic flux density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Under carefully chosen conditions the following effects can be promoted: (i) a more uniform deposit morphology (microscopic as well as macroscopic) [27,31,33,39,[40][41][42][43], (ii) inhibition of dendrite growth [37,44], (iii) change in macrostress of the deposit [45], (iv) increased hardness of the deposit [29,41,46], (v) a more uniform current distribution [47,48], (vi) increased corrosion resistance [28,29] and (vii) composition shift in alloy plating [46].…”
Section: Cathodic Deposit Morphology Effectsmentioning
confidence: 99%
“…Under carefully chosen conditions the following effects can be promoted: (i) a more uniform deposit morphology (microscopic as well as macroscopic) [27,31,33,39,[40][41][42][43], (ii) inhibition of dendrite growth [37,44], (iii) change in macrostress of the deposit [45], (iv) increased hardness of the deposit [29,41,46], (v) a more uniform current distribution [47,48], (vi) increased corrosion resistance [28,29] and (vii) composition shift in alloy plating [46].…”
Section: Cathodic Deposit Morphology Effectsmentioning
confidence: 99%
“…The flow that results from F MHD is generally referred to as a magnetohydrodynamic (MHD) flow. MHD flows are readily observed in both uniform and nonuniform magnetic fields and are being investigated in several laboratories. Our laboratory has very recently demonstrated that MHD flows can be generated in nanoliter volumes of solution adjacent to the surface of a disk-shaped ultramicroelectrode (UME) and that this flow results in a significant enhancement or diminishment of the electrochemical current. …”
Section: Introductionmentioning
confidence: 99%
“…Conditions of 3D-gradient fields can easily be generated for instance in large-scale electrolytic cells by inclined electrodes 102,103 and a solenoidal-type winding of cables carrying electric current. In Cartesian coordinates, the magnitude of the magnetic flux density at an arbitrary (x, y, z) coordinate position in the cell is given by the modulus equation where the subscripted variables denote the flux-density vector components in the indicated spatial directions.…”
Section: Magnetoelectrolytic Mass Transport In a Magnetic Field Gradientmentioning
confidence: 99%